A corrosion-resistant conductive coating and its preparation method and application
By preparing a corrosion-resistant conductive coating composed of a metal base layer, a conversion layer and a doped amorphous carbon layer on a metal bipolar plate, the problem of taking into account both corrosion resistance and conductivity in the prior art is solved, and the problem of considering both corrosion resistance and conductivity is significantly improved The corrosion resistance and conductivity of the coating are suitable for the application of hydrogen fuel cells in acidic and humid environments.
Patent Information
- Application Number
- CN202310031476.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-10
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-01-10
AI Technical Summary
In the prior art, corrosion-resistant conductive coatings cannot take into account both high corrosion resistance and high conductivity, resulting in the metal bipolar plate being easily corroded in acidic and humid environments, reducing fuel cell efficiency.
The corrosion-resistant conductive coating consisting of metal base layer, conversion layer and doped amorphous carbon layer is used to prepare the metal base layer and conversion layer through high-power pulse magnetron sputtering, combining high-power and DC pulse magnetron co-sputtering A doped corrosion-resistant amorphous carbon layer was prepared to form a layered unit structure to enhance the corrosion resistance of the coating.
The corrosion resistance of the coating is significantly enhanced without sacrificing conductivity, the durability and corrosion resistance of the metal bipolar plate are improved, and the working requirements of hydrogen fuel cells in acidic and humid environments are met.
Smart Images

Figure CN116145080B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hydrogen fuel cell bipolar plate coatings, and in particular to a corrosion-resistant conductive coating and a preparation method and application thereof. Background Art
[0002] As one of the main components of proton exchange membrane hydrogen fuel cells, bipolar plates account for 80% of the weight and 45% of the cost of fuel cells. Among them, compared with graphite and composite bipolar plates, metal bipolar plates have good mechanical strength, processing performance and conductivity. Especially considering the transportation scenario, metal bipolar plates are more resistant to mechanical shock and vibration caused by reaction gas rupture and leakage. In addition, metal bipolar plates have also improved their competitiveness in the fuel cell market with their low-cost advantages.
[0003] However, metals are susceptible to corrosion in acidic and humid environments. According to investigations, metal bipolar plates may dissolve when operating in fuel cells with a pH value of 2 to 4 and a temperature of about 80°C. In addition, free metal ions may poison the membrane electrode assembly and reduce the power output of the fuel cell. In addition, the oxide layer formed during corrosion increases the resistivity of the metal bipolar plate. As the oxide layer grows further, the efficiency of the fuel cell will be greatly reduced. Therefore, the performance of the metal bipolar plate substrate alone cannot meet the use requirements of the fuel cell for the time being.
[0004] In order to enhance the corrosion resistance of metal bipolar plates as much as possible without sacrificing their electrical conductivity, people generally use coating technology to give metal bipolar plates good electrical conductivity and corrosion resistance. Carbon coating materials have won the favor of research technicians due to their high performance and low cost. Amorphous carbon coating is a type of carbon coating. Because its carbon atoms have sp 2 With sp 3 The two hybrid types have the properties of both graphite and diamond, so they can be used in the field of metal bipolar plate coating protection. At present, people mainly optimize the process parameters of vapor deposition to regulate the sp in amorphous carbon. 2 With sp 3 Hybridization ratio, so that its conductivity and corrosion resistance to achieve a balance. However, relying solely on this method will result in limited coating performance improvement and the effect is not obvious, such as the corrosion resistance of the coating is improved but the conductivity is significantly reduced. Summary of the invention
[0005] The purpose of the present invention is to overcome the above technical deficiencies, propose a corrosion-resistant conductive coating and a preparation method thereof, and solve the technical problem that the corrosion-resistant conductive coating in the prior art cannot have both high corrosion resistance and high conductivity.
[0006] In the first aspect, the present invention provides a corrosion-resistant conductive coating, which is arranged in sequence from the inside to the outside: a metal base layer, a conversion layer and a doped amorphous carbon layer; wherein the doped amorphous carbon layer includes a doped corrosion-resistant amorphous carbon layer and a doped conductive amorphous carbon layer, and the doped corrosion-resistant amorphous carbon layer is a layered unit structure in which a dense layer and a loose layer are alternately arranged; the metal base layer and the conversion layer are prepared by high-power pulsed magnetron sputtering, and the doped amorphous carbon layer is prepared by high-power pulse and DC pulsed magnetron co-sputtering.
[0007] In a second aspect, the present invention provides a method for preparing a corrosion-resistant conductive coating, comprising the following steps:
[0008] Depositing a metal primer layer on the substrate surface by high-power pulsed magnetron sputtering;
[0009] Depositing a conversion layer on the surface of the metal primer layer by high-power pulsed magnetron sputtering;
[0010] A doped corrosion-resistant amorphous carbon layer and a doped conductive amorphous carbon layer with a layered structure are sequentially deposited on the surface of the conversion layer by high-power pulse and DC pulse magnetron co-sputtering; wherein, the carbon target is connected to a high-power pulse power supply, and the doped metal target is connected to a DC pulse power supply, and the layered unit design of the doped corrosion-resistant amorphous carbon layer is performed by adjusting the bias voltage.
[0011] In a third aspect, the present invention provides an application of a corrosion-resistant conductive coating, wherein the corrosion-resistant conductive coating is applied to a metal bipolar plate of a hydrogen fuel cell.
[0012] Compared with the prior art, the beneficial effects of the present invention include:
[0013] The present invention arranges amorphous carbon functional partitions, doped corrosion-resistant amorphous carbon layers and doped conductive amorphous carbon layers, and constructs layered units of doped corrosion-resistant amorphous carbon layers. It combines high-power pulse and DC pulse co-sputtering to prepare the doped corrosion-resistant amorphous carbon layer, thereby strengthening the overall structure of the doped corrosion-resistant coating, and ultimately achieving the goal of significantly enhancing the corrosion resistance of the coating without sacrificing the conductive properties of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 A schematic diagram of the structure of an embodiment of a corrosion-resistant conductive coating of the present invention;
[0015] Figure 2 The graph is a test result of the coating adhesion prepared by Comparative Examples 1 to 4 and Examples 1 to 3 of the present invention;
[0016] Figure 3 The test results of the contact resistance between the coatings and the carbon paper prepared in Comparative Examples 1 to 4 and Examples 1 to 3 of the present invention are shown;
[0017] Figure 4The coatings prepared in Comparative Examples 1 to 4 and Examples 1 to 3 of the present invention were prepared at a temperature of 80°C and contained 0.1 ppm F - The corrosion current density results of the mesopotential test under the condition of 0.5M H2SO4 electrolyte solution and air flow;
[0018] Figure 5 The coatings prepared in Comparative Examples 1 to 4 and Examples 1 to 3 of the present invention were prepared at a temperature of 80°C and contained 0.1 ppm F - The corrosion current density results of the constant potential test in a 0.5M H2SO4 electrolyte solution with air flowing. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0020] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0021] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0022] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0023] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0024] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0025] See also Figure 1 In the first aspect, the present invention provides a corrosion-resistant conductive coating, which is arranged in sequence from the inside to the outside as a metal base layer, a conversion layer and a doped amorphous carbon layer; wherein the doped amorphous carbon layer includes a doped corrosion-resistant amorphous carbon layer and a doped conductive amorphous carbon layer, and the doped corrosion-resistant amorphous carbon layer is a layered unit structure in which dense layers and loose layers are alternately arranged; the metal base layer and the conversion layer are prepared by high-power pulsed magnetron sputtering, and the doped amorphous carbon layer is prepared by high-power pulse and DC pulsed magnetron co-sputtering.
[0026] In the present invention, the purpose of setting a metal base layer is to enhance the bonding force between the membrane and the substrate and improve the durability of the metal bipolar plate; the purpose of setting a conversion layer is to reduce the internal stress of the coating, enhance the bonding performance, and prevent adverse reactions at the same time; the purpose of setting a doped corrosion-resistant amorphous carbon layer with a layered unit structure is: on the one hand, doping amorphous carbon with corrosion-resistant elements can effectively enhance its corrosion resistance; on the other hand, constructing a layered unit structure by adjusting the bias voltage can effectively slow down the diffusion rate of the corrosive medium and further enhance the corrosion resistance of the corrosion-resistant amorphous carbon layer; the purpose of setting a corrosion-resistant conductive amorphous carbon layer is mainly to give the outer amorphous carbon coating excellent conductivity by doping with conductive elements.
[0027] In the present invention, the doped corrosion-resistant amorphous carbon layer adopts a layered unit structure design, and the layered unit structure design of the doped corrosion-resistant amorphous carbon coating is mainly carried out by adjusting the bias voltage. Among them, the structure of the doped corrosion-resistant amorphous carbon coating prepared under relatively high bias conditions is relatively dense, and the structure of the doped corrosion-resistant amorphous carbon coating prepared under relatively low bias conditions is relatively loose. This "dense-loose-dense" layered unit structure design can be used as a buffer zone for the corrosive medium to enter the substrate, increase the diffusion path of the corrosive liquid medium, delay the time for the corrosive liquid medium to reach the substrate, and achieve the purpose of secondary enhancement of the corrosion resistance of the coating from the perspective of the physical structure of the coating (doping the amorphous carbon layer with corrosion-resistant elements is considered from the perspective of electrochemical corrosion protection, as a way to enhance the corrosion resistance of the coating once).
[0028] High-power pulse (HiPIMS) magnetron sputtering has the advantages of high ionization rate, dense stacking and strong film-base bonding, and can inhibit the growth of columnar structures inside the coating. The present invention uses high-power pulse magnetron sputtering to prepare metal primers and conversion layers. On the one hand, it can prepare metal primers and conversion layers without columnar structures and dense to hinder the corrosive medium flowing out from the amorphous carbon grain boundaries and slow down the corrosion rate; on the other hand, it can strengthen the bonding between the amorphous carbon layer and the substrate, further improving the durability of the metal bipolar plate.
[0029] It should be noted that the film layer of the amorphous carbon layer is relatively thick (between 500 and 2000nm), and high-power pulse magnetron sputtering alone cannot meet the production efficiency requirements. Therefore, the present invention can significantly improve the deposition rate by using high-power pulse and DC pulse magnetron co-sputtering. It is worth noting that when the present invention uses high-power pulse and DC pulse magnetron co-sputtering, the carbon target is connected to the high-power pulse power supply, and the doped metal target (such as Mo, W, Ag, Au, etc.) is connected to the DC pulse power supply. The reason for this design is: on the one hand, the carbon atom ionization rate of the carbon material can be improved by high-power pulses; on the other hand, the doped metal target connected to the DC pulse can form high-power pulse and DC pulse magnetron co-sputtering, thereby improving the deposition rate of the doped corrosion-resistant conductive amorphous carbon coating. The doped corrosion-resistant amorphous carbon coating is also designed by adjusting the bias voltage for layered structure design, and each layer unit is prepared by different bias voltages, so as to form a "dense-loose-dense" layered unit structure through high and low bias voltages, so as to increase the penetration path and residence time of the corrosive medium, and achieve the purpose of enhancing the corrosion performance.
[0030] In this embodiment, each layered unit of the doped corrosion-resistant amorphous carbon layer is composed of alternating high bias layers and low bias layers, and includes n units in total, where n≥2, and further ranges from 3 to 15.
[0031] In this embodiment, the selection of the base element Me is determined by the actual metal bipolar plate substrate material, and metal elements with a thermal expansion coefficient close to that of the metal bipolar plate substrate material are preferably selected, such as one or more of Ti, Cr, Nb, etc.; the conversion layer is at least one of the nitrogen-doped compounds Me / N (such as Ti / N, Cr / N, Nb / N, etc.) of the base element Me and the nitrogen-doped carbides Me / C / N (such as Ti / C / N, Cr / C / N, Nb / C / N, etc.) of the base element Me; the doping elements of the corrosion-resistant amorphous carbon layer are corrosion-resistant metal elements that are beneficial to improving the corrosion resistance, such as one or more of W, Mo, N, etc., and the doping elements of the conductive amorphous carbon layer are conductive metal elements that are beneficial to improving the conductivity, such as one or more of Au, Ag, Cu, etc.
[0032] In this embodiment, the thickness of the metal base layer is 5 to 20 nm, including but not limited to 5 nm, 10 nm, 15 nm, 20 nm, etc.; the thickness of the conversion layer is 10 to 60 nm, including but not limited to 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, etc.; the thickness of the doped amorphous carbon layer is 500 to 2000 nm, including but not limited to 500 nm, 1000 nm, 1500 nm, 2000 nm, etc.
[0033] In some specific embodiments of the present invention, the conversion layer includes a conversion layer Me / N and a conversion layer Me / C / N. Further, the thickness of the conversion layer Me / N is 1% to 99% of the total thickness of the conversion layer, including but not limited to 1%, 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 95%, 99%, etc.; the thickness of the doped corrosion-resistant amorphous carbon layer is 1% to 99% of the total thickness of the doped amorphous carbon layer, including but not limited to 1%, 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 95%, 99%, etc.
[0034] In this embodiment, the base material is selected from any one of stainless steel (such as 304 stainless steel, 310 stainless steel, 316 stainless steel, 316L stainless steel, 904L stainless steel, etc.), metal titanium, titanium alloy (such as α titanium alloy, α+β titanium alloy, etc.), metal nickel, nickel alloy (such as nickel-based high-temperature alloy, nickel-based corrosion-resistant alloy, nickel-based wear-resistant alloy, etc.), metal aluminum and aluminum alloy (such as Al-Cu alloy, Al-Mn alloy, Al-Si alloy, Al-Li alloy, etc.).
[0035] In a second aspect, the present invention provides a method for preparing a corrosion-resistant conductive coating, comprising the following steps:
[0036] A metal base layer is deposited on the substrate surface by high-power pulsed magnetron sputtering;
[0037] The conversion layer is deposited on the surface of the metal base layer by high-power pulsed magnetron sputtering;
[0038] The doped corrosion-resistant amorphous carbon layer and the doped conductive amorphous carbon layer with a layered structure are sequentially deposited on the surface of the conversion layer by high-power pulse and DC pulse magnetron co-sputtering. The carbon target is connected to a high-power pulse power supply, and the doped metal target (such as Mo, W, Ag, Au, etc.) is connected to a DC pulse power supply, and the layered unit design of the doped corrosion-resistant amorphous carbon layer is carried out by adjusting the bias voltage.
[0039] In this embodiment, the step of depositing a metal base layer on the substrate surface by high-power pulsed magnetron sputtering includes:
[0040] Introduce argon gas, turn on the base metal target and connect to a high-power pulse power supply, and deposit the metal base on the substrate surface by high-power pulse magnetron sputtering. The chamber pressure is maintained at 0.1-0.6Pa, including but not limited to 0.1Pa, 0.2Pa, 0.3Pa, 0.4Pa, 0.5Pa, 0.6Pa, etc. The frequency of the high-power pulse power supply is 100-800Hz, including but not limited to 100Hz, 200Hz, 300Hz, 400Hz, 500Hz, 600Hz, 700Hz, 800Hz, etc. The pulse width is 50-800μs, including but not limited to 50μs, 100μs, 200μs, 300μs, 400μs, 500μs, 600μs, 700μs, 800μs, etc. The power is 1 .0~5.0kW, including but not limited to 1.0kW, 2.0kW, 3.0kW, 4.0kW, 5.0kW, etc., the substrate bias is -100~-900V, including but not limited to -100V, -200V, -300V, -400V, -500V, -600V, -700V, -800V, -900V, etc., the deposition temperature is 20~400℃, including but not limited to 20℃, 50℃, 100℃, 200℃, 300℃, 400℃, etc., the deposition time is 5~20min, including but not limited to 5min, 10min, 15min, 20min, etc.
[0041] In this embodiment, the step of depositing a conversion layer on the surface of the metal base layer by high-power pulsed magnetron sputtering includes:
[0042] S21. After the deposition of the metal base layer Me is completed, nitrogen N2 is immediately introduced to deposit a conversion layer Me / N on the surface of the metal base layer Me by high-power pulsed magnetron sputtering; wherein the flow ratio of nitrogen to argon is 1:(1-2), and the chamber pressure is maintained at 0.2-0.9Pa, including but not limited to 0.1Pa, 0.2Pa, 0.3Pa, 0.4Pa, 0.5Pa, 0.6Pa, 0.7Pa, 0.8Pa, 0.9Pa, etc. The sputtering parameters and deposition temperature of the base layer element metal target are consistent with those of the deposited metal base layer, and the deposition time is 5-20min, including but not limited to 5min, 10min, 15min, 20min, etc.;
[0043] S22, turn on the carbon target and connect to a high-power pulse power supply, and deposit a conversion layer Me / C / N on the conversion layer Me / N by high-power pulse magnetron sputtering; wherein the gas flow rate, the sputtering parameters of the base metal target, and the deposition temperature are all consistent with those of the deposited conversion layer Cr / N; the power supply frequency of the carbon target is set to 50-600 Hz, including but not limited to 50 Hz, 100 Hz, 200 Hz, 300 Hz, 400 Hz, 500 Hz, 600 Hz, etc., and the pulse width is 50-1000 μs, including but not limited to 50 μs, 100 μs, 200 μs, 300 μs, 400 μs, 50 0μs, 600μs, 700μs, 800μs, 900μs, 1000μs, etc., the power is 0.5~3.0kW, including but not limited to 0.5kW, 1.0kW, 2.0kW, 3.0kW, 4.0kW, 5.0kW, etc.; the substrate bias is -100~-500V, including but not limited to -100V, -200V, -300V, -400V, -500V, etc., to avoid excessive bias which may make the carbon film structure loose and fall off; the deposition time is 5~20min, including but not limited to 5min, 10min, 15min, 20min, etc.
[0044] In this embodiment, the steps of sequentially depositing a doped corrosion-resistant amorphous carbon layer and a doped conductive amorphous carbon layer having a layered structure on the surface of the conversion layer by high-power pulse and DC pulse magnetron co-sputtering include:
[0045] S31. After the deposition of the conversion layer is completed, the base metal target and nitrogen are turned off, the doped corrosion-resistant metal target is turned on and a DC pulse current is connected, and a doped corrosion-resistant amorphous carbon layer is deposited on the surface of the conversion layer by high-power pulse and DC pulse magnetron co-sputtering, and a layered unit design is performed by adjusting the substrate bias voltage; wherein the chamber pressure is maintained at 0.1-0.9Pa, including but not limited to 0.1Pa, 0.2Pa, 0.3Pa, 0.4Pa, 0.5Pa, 0.6Pa, 0.7Pa, 0.8Pa, 0.9Pa, etc.; the current of the doped corrosion-resistant metal target is 5-30A, including but not limited to 5A, 10A, 15A, 20A, 30A, etc., and the pulse frequency is 50-600kHz, including but not limited to 50H z, 100Hz, 200Hz, 300Hz, 400Hz, 500Hz, 600Hz, etc., the pulse width is 25-300μs, including but not limited to 25μs, 50μs, 75μs, 100μs, 200μs, 300μs; the carbon target sputtering parameters and deposition temperature are consistent with the deposition conversion layer; the substrate bias is alternating between high and low bias, and its variation range is -100 to -900V, including but not limited to -100V, -200V, -300V, -400V, -500V, -600V, -700V, -800V, -900V, etc., and the total deposition time is 30-60min, including but not limited to 30min, 40min, 50min, 60min. In some specific embodiments of the present invention, the substrate bias is set as follows: increase the bias from -300V to -600V, and deposit for 1 to 20 minutes; then adjust the bias from -600V to -300V, and deposit for 1 to 20 minutes; then increase the bias from -300V to -600V, and deposit for 1 to 20 minutes, and repeat the above process until the doped corrosion-resistant amorphous carbon layer is deposited.
[0046] S32. After the deposition of the doped corrosion-resistant amorphous carbon layer is completed, the doped corrosion-resistant metal target is turned off, the doped conductive metal target is turned on and a DC pulse power supply is connected, and a doped conductive amorphous carbon layer is deposited on the surface of the doped corrosion-resistant amorphous carbon layer by high-power pulse and DC pulse magnetron co-sputtering. Wherein, the chamber pressure is maintained at 0.1-0.9Pa, including but not limited to 0.1Pa, 0.2Pa, 0.3Pa, 0.4Pa, 0.5Pa, 0.6Pa, 0.7Pa, 0.8Pa, 0.9Pa, etc.; the current of the conductive layer element metal target is 5-30A, including but not limited to 5A, 10A, 15A, 20A, 30A, etc., the pulse frequency is 50-600kHz, including but not limited to 50Hz, 100Hz, 200Hz, 300Hz, 400Hz, 500Hz, 600Hz, etc., the pulse width is 25-300μs, including but not limited to 25μs, 50μs, 75μs, 100μs, 200μs, 300μs; the carbon target sputtering parameters and substrate bias are consistent with the deposition conversion layer; the deposition temperature is 200-400℃, including but not limited to 200℃, 300℃, 400℃, etc., and the increase in temperature can promote the amorphous carbon sp 2 The increase in content is beneficial to the conductive performance of the coating; the deposition time is 30 to 60 minutes, including but not limited to 30 minutes, 40 minutes, 50 minutes, 60 minutes, etc.
[0047] In this embodiment, the carbon target is a graphite target.
[0048] In this embodiment, before use, the substrate needs to be cleaned to remove impurities such as oxide film and grease on the surface of the substrate.
[0049] In some embodiments of the present invention, the cleaning process comprises:
[0050] The substrate surface is polished to remove the surface oxide layer, and then ultrasonically cleaned with acetone, anhydrous ethanol and deionized water for 10 to 60 minutes in sequence to remove grease and impurities on the material surface. After drying, the surface oxide film is removed by sputtering cleaning and the substrate surface is activated. During the sputtering cleaning process, the chamber pressure is 0.1 to 1.0 Pa, including but not limited to 0.1 Pa, 0.2 Pa, 0.3 Pa, 0.4 Pa, 0.5 Pa, 0.6 Pa, 0.7 Pa, 0.8 Pa, 0.9 Pa, 1 Pa, etc.; the applied voltage is -300 to -900 V, including but not limited to -300 V, -400 V, -500 V, -600 V, -700 V, -800 V, -900 V, etc., and the cleaning time is 10 to 60 min, including but not limited to 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, etc.
[0051] In this embodiment, after the deposition process of the doped conductive amorphous carbon layer is completed, the process further includes: turning off the carbon target, the conductive metal target and the heating device, and cooling the target to room temperature in an argon atmosphere.
[0052] In a third aspect, the present invention provides an application of a corrosion-resistant conductive coating, wherein the corrosion-resistant conductive coating is applied to a metal bipolar plate of a hydrogen fuel cell.
[0053] Comparative Example 1
[0054] A method for preparing a corrosion-resistant conductive coating, the method comprising the following steps:
[0055] (1) First, a 316L stainless steel sheet with a size of 50 mm × 50 mm × 0.1 mm was selected as the metal bipolar plate substrate, and its surface was polished to remove the surface oxide layer, and then ultrasonically cleaned in acetone, anhydrous ethanol and deionized water for 30 min in sequence to remove surface grease and impurities, and then dried and loaded into the furnace;
[0056] (2) Then, the chamber was evacuated to a vacuum of 5 × 10 -4 Pa, introduce argon Ar to keep the pressure at 0.20-0.25Pa, adjust the speed to 2r / min, apply -900V bias, and glow clean for 30min to remove the oxide layer and impurities on the surface of 316L stainless steel substrate and activate its surface;
[0057] (3) After the glow cleaning is completed, turn off the argon gas Ar and bias voltage to restore the vacuum inside the chamber to 5×10 -4 Pa below, ready to deposit metal base layer;
[0058] (4) Then, argon gas Ar was introduced and the pressure was maintained at 0.15-0.20 Pa, and then the Cr target was turned on and connected to a DC pulse power supply. The DC pulse power supply current of the Cr target was set to 25 A, the pulse frequency was set to 300 kHz, and the pulse width was set to 75 μs. At the same time, the substrate bias voltage was set to -650 V, and the deposition temperature was set to 25°C. The metal Cr base layer was deposited on the surface of the 316L substrate by high-power pulsed magnetron sputtering of the Cr target for 10 min.
[0059] (5) Then, nitrogen N2 is introduced, and the flow ratio of nitrogen N2 to argon Ar is adjusted to 2:3 (the pressure is maintained at 0.20-0.25 Pa), and the parameters such as Cr target sputtering parameters, bias voltage, and deposition temperature are kept unchanged (see step 4), and a conversion layer Cr / N is deposited on the surface of the metal Cr base layer for 8 min;
[0060] (6) Next, the graphite target is turned on and a DC pulse power supply is connected at the same time. The DC pulse power supply current of the graphite target is set to 5 A, the pulse frequency is 300 kHz, and the pulse width is 75 μs. The substrate bias voltage is reduced to -300 V (to avoid excessive bias voltage causing the carbon film structure to become loose and fall off). The Cr target sputtering parameters, gas flow rate, deposition temperature and other parameters are kept unchanged (see step 5). The conversion layer Cr / C / N is deposited on the surface of the conversion layer Cr / N for 5 min.
[0061] (7) After the conversion layer is completely deposited, turn off the Cr target and nitrogen N2, adjust the Ar flow rate to maintain the pressure at 0.15-0.20 Pa, and prepare to deposit the amorphous carbon layer;
[0062] (8) Then, keeping the graphite target sputtering parameters and deposition temperature unchanged (see step 6), high-power pulsed sputtering is performed to deposit an amorphous carbon layer on the surface of the conversion layer Cr / C / N for 75 min;
[0063] (9) Finally, the graphite target and the heating device are turned off and cooled to room temperature in an argon atmosphere to complete the preparation of the corrosion-resistant conductive coating.
[0064] The test results show that the coating bonding force is 15N and the contact resistance with carbon paper is 8.3mΩcm 2 (1.4MPa); and at a temperature of 80°C, containing 0.1ppmF - Under the condition of 0.5M H2SO4 electrolyte solution and air flow, the self-corrosion current density after the dynamic potential test was 1.24μA / cm 2 After 10h of polarization test at constant potential 0.6V (vs.SCE), the corrosion current was 5.12μA / cm 2 .
[0065] Comparative Example 2
[0066] A method for preparing a corrosion-resistant conductive coating, the method comprising the following steps:
[0067] (1) First, a 316L stainless steel sheet with a size of 50 mm × 50 mm × 0.1 mm was selected as the metal bipolar plate substrate, and its surface was polished to remove the surface oxide layer, and then ultrasonically cleaned in acetone, anhydrous ethanol and deionized water for 30 min in sequence to remove surface grease and impurities, and then dried and loaded into the furnace;
[0068] (2) Then, the chamber was evacuated to a vacuum of 5 × 10 -4 Pa, introduce argon Ar to keep the pressure at 0.20-0.25Pa, adjust the speed to 2r / min, apply -900V bias, and glow clean for 30min to remove the oxide layer and impurities on the surface of 316L stainless steel substrate and activate its surface;
[0069] (3) After the glow cleaning is completed, turn off the argon gas Ar and bias voltage to restore the vacuum inside the chamber to 5×10 -4 Pa below, ready to deposit metal base layer;
[0070] (4) Then, argon gas Ar was introduced and the pressure was maintained at 0.15-0.20 Pa, and then the Cr target was turned on and connected to a high-power pulse power supply. The frequency of the Cr target high-power pulse power supply was set to 400 Hz, the pulse width was 600 μs, and the power was 3.0 kW. At the same time, the substrate bias was set to -650 V, and the deposition temperature was set to 50 ° C. The metal Cr base layer was deposited on the surface of the 316L substrate by high-power pulse magnetron sputtering of the Cr target for 10 min;
[0071] (5) Then, nitrogen N2 is introduced, and the flow ratio of nitrogen N2 to argon Ar is adjusted to 2:3 (the pressure is maintained at 0.20-0.25 Pa), the Cr target sputtering parameters and deposition temperature are kept unchanged (see step 4), and a conversion layer Cr / N is deposited on the surface of the metal Cr base layer for 8 min;
[0072] (6) Next, the graphite target is turned on and a high-power pulse power supply is connected at the same time. The frequency of the high-power pulse power supply of the graphite target is set to 500 Hz, the pulse width is 300 μs, and the power is 2.0 kW. The substrate bias voltage is reduced to -300 V (to avoid excessive bias voltage causing the carbon film structure to become loose and fall off). The sputtering parameters, gas flow rate, deposition temperature and other parameters of the Cr target are kept unchanged (see step 5). The conversion layer Cr / C / N is deposited on the surface of the conversion layer Cr / N for 5 min.
[0073] (7) After the conversion layer is completely deposited, turn off the Cr target and nitrogen N2, adjust the Ar flow rate to maintain the pressure at 0.15-0.20 Pa, and prepare to deposit the amorphous carbon layer;
[0074] (8) Then, keeping the graphite target sputtering parameters and deposition temperature unchanged (see step 6), high-power pulsed sputtering is performed to deposit an amorphous carbon layer on the surface of the conversion layer Cr / C / N for 75 min;
[0075] (9) Finally, the graphite target and the heating device are turned off and cooled to room temperature in an argon atmosphere to complete the preparation of the corrosion-resistant conductive coating.
[0076] The test results show that the coating bonding force is 27N and the contact resistance with carbon paper is 9.2mΩcm 2 (1.4MPa); and at a temperature of 80°C, containing 0.1ppmF - Under the condition of 0.5M H2SO4 electrolyte solution and air flow, the self-corrosion current density after the dynamic potential test is 0.75μA / cm2 After 10h of polarization test at constant potential 0.6V (vs.SCE), the corrosion current was 1.88μA / cm 2 .
[0077] It can be seen from Comparative Examples 1 and 2 that the use of high-power pulsed magnetron sputtering to prepare corrosion-resistant conductive coatings can significantly improve the adhesion and corrosion resistance of the coatings, and enhance the durability and stability of the coatings, but will have a certain impact on the conductivity of the coatings.
[0078] Comparative Example 3
[0079] A method for preparing a corrosion-resistant conductive coating, the method comprising the following steps:
[0080] (1) First, a 316L stainless steel sheet with a size of 50 mm × 50 mm × 0.1 mm was selected as the metal bipolar plate substrate, and its surface was polished to remove the surface oxide layer, and then ultrasonically cleaned in acetone, anhydrous ethanol and deionized water for 30 min in sequence to remove surface grease and impurities, and then dried and loaded into the furnace;
[0081] (2) Then, the chamber was evacuated to a vacuum of 5 × 10 -4 Pa, introduce argon Ar to keep the pressure at 0.20-0.25Pa, adjust the speed to 2r / min, apply -900V bias, and glow clean for 30min to remove the oxide layer and impurities on the surface of 316L stainless steel substrate and activate its surface;
[0082] (3) After the glow cleaning is completed, turn off the argon gas Ar and bias voltage to restore the vacuum inside the chamber to 5×10 -4 Pa below, ready to deposit metal base layer;
[0083] (4) Then, argon gas Ar was introduced and the pressure was maintained at 0.15-0.20 Pa, and then the Cr target was turned on and connected to a high-power pulse power supply. The power supply frequency of the Cr target was set to 400 Hz, the pulse width was 600 μs, the power was 3.0 kW, the substrate bias was set to -650 V, and the deposition temperature was 50°C. The metal Cr base layer was deposited on the surface of the 316L substrate by high-power pulse magnetron sputtering of the Cr target for 10 min.
[0084] (5) Then, nitrogen N2 is introduced, and the flow ratio of nitrogen N2 to argon Ar is adjusted to 2:3 (the pressure is maintained at 0.20-0.25 Pa), the Cr target sputtering parameters and deposition temperature are kept unchanged (see step 4), and a conversion layer Cr / N is deposited on the surface of the metal Cr base layer for 8 min;
[0085] (6) Next, the graphite target is turned on and a high-power pulse power supply is connected at the same time. The power supply frequency of the graphite target is set to 500 Hz, the pulse width is 300 μs, and the power is 2.0 kW. The substrate bias voltage is reduced to -300 V (to avoid excessive bias voltage causing the carbon film structure to become loose and fall off). The Cr target sputtering parameters, gas flow rate, and deposition temperature are kept unchanged (see step 5). The conversion layer Cr / C / N is deposited on the surface of the conversion layer Cr / N for 5 min.
[0086] (7) After the conversion layer is completely deposited, turn off the Cr target and nitrogen N2, adjust the Ar flow rate to maintain the pressure at 0.15-0.20 Pa, and prepare to deposit the amorphous carbon layer;
[0087] (8) Then, keeping the graphite target sputtering parameters unchanged (see step 6), the deposition temperature was increased from 50°C to 300°C (the increase in temperature can promote the formation of amorphous carbon sp 2 The content increases, which is beneficial to the conductive properties of the coating). A high-power pulse sputtering deposition of an amorphous carbon layer is achieved on the surface of the conversion layer Cr / C / N, and the deposition time is 75 minutes.
[0088] (9) Finally, the graphite target and the heating device are turned off and cooled to room temperature in an argon atmosphere to complete the preparation of the corrosion-resistant conductive coating.
[0089] The test results show that the coating bonding force is 23N and the contact resistance with carbon paper is 5.7mΩcm 2 (1.4MPa); and at a temperature of 80°C, containing 0.1ppmF - Under the condition of 0.5M H2SO4 electrolyte solution and air flow, the self-corrosion current density after the dynamic potential test was 1.15μA / cm 2 After 10h of polarization test at 0.6V (vs. SCE), the corrosion current was 2.74μA / cm 2 .
[0090] It can be seen from Comparative Examples 2 and 3 that by changing the coating process, such as increasing the amorphous carbon deposition temperature, the conductive properties of the coating can be effectively improved, but at the same time it will also have a certain impact on the corrosion resistance of the coating.
[0091] Comparative Example 4
[0092] A method for preparing a corrosion-resistant conductive coating, the method comprising the following steps:
[0093] (1) First, a 316L stainless steel sheet with a size of 50 mm × 50 mm × 0.1 mm was selected as the metal bipolar plate substrate, and its surface was polished to remove the surface oxide layer, and then ultrasonically cleaned in acetone, anhydrous ethanol and deionized water for 30 min in sequence to remove surface grease and impurities, and then dried and loaded into the furnace;
[0094] (2) Then, the chamber was evacuated to a vacuum of 5 × 10 -4 Pa, introduce argon Ar to keep the pressure at 0.20-0.25Pa, adjust the speed to 2r / min, apply -900V bias, and glow clean for 30min to remove the oxide layer and impurities on the surface of 316L stainless steel substrate and activate its surface;
[0095] (3) After the glow cleaning is completed, turn off the argon gas Ar and bias voltage to restore the vacuum inside the chamber to 5×10 -4 Pa below, ready to deposit metal base layer;
[0096] (4) Then, argon gas Ar was introduced and the pressure was maintained at 0.15-0.20 Pa, and then the Cr target was turned on and connected to a high-power pulse power supply. The power supply frequency of the Cr target was set to 400 Hz, the pulse width was 600 μs, the power was 3.0 kW, the substrate bias was set to -650 V, and the deposition temperature was 50°C. The metal Cr base layer was deposited on the surface of the 316L substrate by high-power pulse magnetron sputtering of the Cr target for 10 min.
[0097] (5) Then, nitrogen N2 is introduced, and the flow ratio of nitrogen N2 to argon Ar is adjusted to 2:3 (the pressure is maintained at 0.20-0.25 Pa), the Cr target sputtering parameters and deposition temperature are kept unchanged (see step 4), and a conversion layer Cr / N is deposited on the surface of the metal Cr base layer for 8 min;
[0098] (6) Next, the graphite target is turned on and a high-power pulse power supply is connected at the same time. The power supply frequency of the graphite target is set to 500 Hz, the pulse width is 300 μs, and the power is 2.0 kW. The substrate bias voltage is reduced to -300 V (to avoid excessive bias voltage causing the carbon film structure to become loose and fall off). The Cr target sputtering parameters, gas flow rate, and deposition temperature are kept unchanged (see step 5). The conversion layer Cr / C / N is deposited on the surface of the conversion layer Cr / N for 5 min.
[0099] (7) After the conversion layer is completely deposited, turn off the Cr target and nitrogen N2, adjust the argon Ar flow rate to maintain the pressure at 0.15-0.20 Pa, and prepare to deposit the doped corrosion-resistant amorphous carbon layer;
[0100] (8) Next, the W target is turned on and connected to a DC pulse power supply, the current of the W target is set to 15 A, the pulse frequency is set to 300 kHz, the pulse width is set to 75 μs, and the graphite target sputtering parameters, bias voltage, and deposition temperature are kept unchanged (see step 6), and a W-doped corrosion-resistant amorphous carbon layer C / W is deposited on the surface of the conversion layer Cr / C / N by high-power pulse and DC pulse magnetron co-sputtering, and the deposition time is 45 min;
[0101] (9) After the doped corrosion-resistant amorphous carbon layer is completely deposited, the W target is turned off, and the Ar flow rate and pressure are maintained at 0.15-0.20 Pa to prepare for the deposition of the doped conductive amorphous carbon layer;
[0102] (10) Then, the Ag target was turned on and a DC pulse power supply was connected. The current of the Ag target was set to 10 A, the pulse frequency was set to 300 kHz, the pulse width was set to 75 μs, and the deposition temperature was increased from 50 °C to 300 °C (the increase in temperature can promote the formation of amorphous carbon sp 2 The content increases, which is beneficial to the conductive properties of the coating), keeping the graphite target sputtering parameters and bias voltage unchanged (see step 6), high-power pulse and DC pulse magnetron co-sputtering deposition of Ag-doped conductive amorphous carbon layer C / Ag on the surface of the W-doped corrosion-resistant amorphous carbon layer, the deposition time is 30min;
[0103] (11) Finally, the graphite target, the Ag target and the heating device are turned off and cooled to room temperature in an argon atmosphere to complete the preparation of the doped corrosion-resistant conductive coating.
[0104] The test results show that the coating bonding force is 28N and the contact resistance with carbon paper is 5.1mΩcm 2 (1.4MPa); and at a temperature of 80°C, containing 0.1ppmF - Under the condition of 0.5M H2SO4 electrolyte solution and air flow, the self-corrosion current density after the dynamic potential test is 0.66μA / cm 2 After 10h of polarization test at 0.6V (vs. SCE), the corrosion current was 1.12μA / cm 2 .
[0105] It can be seen from Comparative Examples 3 and 4 that by setting functional partitions in the amorphous carbon coating (such as a doped corrosion-resistant amorphous carbon layer and a doped conductive amorphous carbon layer), it is possible to ensure the conductivity of the outer amorphous carbon layer while effectively enhancing the corrosion resistance of the entire coating.
[0106] Example 1
[0107] A method for preparing a corrosion-resistant conductive coating, the method comprising the following steps:
[0108] (1) First, a 316L stainless steel sheet with a size of 50 mm × 50 mm × 0.1 mm was selected as the metal bipolar plate substrate, and its surface was polished to remove the surface oxide layer, and then ultrasonically cleaned in acetone, anhydrous ethanol and deionized water for 30 min in sequence to remove surface grease and impurities, and then dried and loaded into the furnace;
[0109] (2) Then, the chamber was evacuated to a vacuum of 5 × 10 -4Pa, introduce argon Ar to keep the pressure at 0.20-0.25Pa, adjust the speed to 2r / min, apply -900V bias, and glow clean for 30min to remove the oxide layer and impurities on the surface of 316L stainless steel substrate and activate its surface;
[0110] (3) After the glow cleaning is completed, turn off the argon gas Ar and bias voltage to restore the vacuum inside the chamber to 5×10 -4 Pa below, ready to deposit metal base layer;
[0111] (4) Then, argon gas Ar was introduced and the pressure was maintained at 0.15-0.20 Pa, and then the Cr target was turned on and connected to a high-power pulse power supply. The power supply frequency of the Cr target was set to 400 Hz, the pulse width was 600 μs, the power was 3.0 kW, the substrate bias was set to -650 V, and the deposition temperature was 50°C. The metal Cr base layer was deposited on the surface of the 316L substrate by high-power pulse magnetron sputtering of the Cr target for 10 min.
[0112] (5) Then, nitrogen N2 is introduced, and the flow ratio of nitrogen N2 to argon Ar is adjusted to 2:3 (the pressure is maintained at 0.20-0.25 Pa), the Cr target sputtering parameters and deposition temperature are kept unchanged (see step 4), and a conversion layer Cr / N is deposited on the surface of the metal Cr base layer for 8 min;
[0113] (6) Next, the graphite target is turned on and a high-power pulse power supply is connected at the same time. The power supply frequency of the graphite target is set to 500 Hz, the pulse width is 300 μs, and the power is 2.0 kW. The substrate bias voltage is reduced to -300 V (to avoid excessive bias voltage causing the carbon film structure to become loose and fall off). The Cr target sputtering parameters, gas flow rate, and deposition temperature are kept unchanged (see step 5). The conversion layer Cr / C / N is deposited on the surface of the conversion layer Cr / N for 5 min.
[0114] (7) After the conversion layer is completely deposited, turn off the Cr target and nitrogen N2, adjust the argon Ar flow rate to maintain the pressure at 0.15-0.20 Pa, and prepare to deposit the doped corrosion-resistant amorphous carbon layer;
[0115] (8) Next, turn on the W target and connect the DC pulse power supply, set the current of the W target to 15A, the pulse frequency to 300kHz, the pulse width to 75μs, keep the graphite target sputtering parameters and deposition temperature unchanged (see step 6), increase the bias voltage from -300V to -600V, and deposit for 5min; then, keep other parameters unchanged, adjust the bias voltage from -600V to -300V, and deposit for 5min; finally, keep other parameters unchanged, increase the bias voltage from -300V to -600V, and deposit for 5min;
[0116] (9) Afterwards, step (8) was repeated three times to obtain a three-layer unit W-doped corrosion-resistant amorphous carbon layer C / W, with a total deposition time of 45 min;
[0117] (10) After the deposition of the doped corrosion-resistant amorphous carbon layer is completed, the W target is turned off, and the Ar flow rate and pressure are maintained at 0.15-0.20 Pa to prepare for the deposition of the doped conductive amorphous carbon layer;
[0118] (11) Then, the Ag target was turned on and a DC pulse power supply was connected. The current of the Ag target was set to 10 A, the pulse frequency was set to 300 kHz, the pulse width was set to 75 μs, and the deposition temperature was increased from 50 °C to 300 °C (the increase in temperature can promote the formation of amorphous carbon sp 2 The content increases, which is beneficial to the conductive properties of the coating), keeping the graphite target sputtering parameters and bias voltage unchanged (see step 6), high-power pulse and DC pulse magnetron co-sputtering deposition of Ag-doped conductive amorphous carbon layer C / Ag on the surface of the W-doped corrosion-resistant amorphous carbon layer, the deposition time is 30min;
[0119] (12) Finally, the graphite target, the Ag target and the heating device are turned off and cooled to room temperature in an argon atmosphere to complete the preparation of the corrosion-resistant conductive coating.
[0120] The test results show that the coating bonding force is 30N and the contact resistance with carbon paper is 4.9mΩcm 2 (1.4MPa); and at a temperature of 80°C, containing 0.1ppmF - Under the condition of 0.5M H2SO4 electrolyte solution and air flow, the self-corrosion current density after the dynamic potential test was 0.31μA / cm 2 After 10h of constant potential 0.6V (vs. SCE) polarization test, the corrosion current is 0.82μA / cm 2 .
[0121] It can be seen from Comparative Example 4 and Example 1 that, on the basis of setting functional partitions in the amorphous carbon coating, different bias voltages are used to set a layered unit structure in the doped corrosion-resistant amorphous carbon coating to form a "dense-loose-dense" layered unit, which can effectively hinder the penetration rate of the corrosive medium and slow down the corrosion rate. Ultimately, the conductive performance of the coating is guaranteed and the corrosion resistance of the coating is enhanced.
[0122] Example 2
[0123] A method for preparing a corrosion-resistant conductive coating, the method comprising the following steps:
[0124] (1) First, pure titanium with a size of 50 mm × 50 mm × 0.1 mm was selected as the metal bipolar plate substrate, and its surface was polished to remove the surface oxide layer, and then ultrasonically cleaned in acetone, anhydrous ethanol and deionized water for 30 min in sequence to remove surface grease and impurities, and then dried and loaded into the furnace;
[0125] (2) Then, the chamber was evacuated to a vacuum of 5 × 10 -4 Pa, introduce argon Ar to keep the pressure at 0.20-0.25Pa, adjust the speed to 2r / min, apply -900V bias, and perform glow cleaning for 30min to remove the oxide layer and impurities on the surface of the pure titanium substrate and activate the surface;
[0126] (3) After the glow cleaning is completed, turn off the argon gas Ar and bias voltage to restore the vacuum inside the chamber to 5×10 -4 Pa below, ready to deposit metal base layer;
[0127] (4) Then, argon gas Ar was introduced and the pressure was maintained at 0.15-0.20 Pa, and then the Cr target was turned on and connected to a high-power pulse power supply. The power supply frequency of the Cr target was set to 400 Hz, the pulse width was 600 μs, the power was 3.0 kW, the substrate bias was set to -650 V, and the deposition temperature was 50°C. The metal Cr base layer was deposited on the surface of the pure titanium substrate by high-power pulse magnetron sputtering of the Cr target for 10 min;
[0128] (5) Then, nitrogen N2 is introduced, and the flow ratio of nitrogen N2 to argon Ar is adjusted to 2:3 (the pressure is maintained at 0.20-0.25 Pa), the Cr target sputtering parameters and deposition temperature are kept unchanged (see step 4), and a conversion layer Cr / N is deposited on the surface of the metal Cr base layer for 8 min;
[0129] (6) Next, the graphite target is turned on and a high-power pulse power supply is connected at the same time. The power supply frequency of the graphite target is set to 500 Hz, the pulse width is 300 μs, and the power is 2.0 kW. The substrate bias voltage is reduced to -300 V (to avoid excessive bias voltage causing the carbon film structure to become loose and fall off). The Cr target sputtering parameters, gas flow rate, and deposition temperature are kept unchanged (see step 5). The conversion layer Cr / C / N is deposited on the surface of the conversion layer Cr / N for 5 min.
[0130] (7) After the conversion layer is completely deposited, turn off the Cr target and nitrogen N2, adjust the argon Ar flow rate to maintain the pressure at 0.15-0.20 Pa, and prepare to deposit the doped corrosion-resistant amorphous carbon layer;
[0131] (8) Next, turn on the W target and connect the DC pulse power supply, set the current of the W target to 15A, the pulse frequency to 300kHz, the pulse width to 75μs, keep the graphite target sputtering parameters and deposition temperature unchanged (see step 6), increase the bias voltage from -300V to -600V, and deposit for 5min; then, keep other parameters unchanged, adjust the bias voltage from -600V to -300V, and deposit for 5min; finally, keep other parameters unchanged, increase the bias voltage from -300V to -600V, and deposit for 5min;
[0132] (9) Afterwards, step (8) was repeated three times to obtain a three-layer unit W-doped corrosion-resistant amorphous carbon layer C / W, with a total deposition time of 45 min;
[0133] (10) After the deposition of the doped corrosion-resistant amorphous carbon layer is completed, the W target is turned off, and the Ar flow rate and pressure are maintained at 0.15-0.20 Pa to prepare for the deposition of the doped conductive amorphous carbon layer;
[0134] (11) Then, the Ag target was turned on and a DC pulse power supply was connected. The current of the Ag target was set to 10 A, the pulse frequency was set to 300 kHz, the pulse width was set to 75 μs, and the deposition temperature was increased from 50 °C to 300 °C (the increase in temperature can promote the formation of amorphous carbon sp 2 The content increases, which is beneficial to the conductive properties of the coating), keeping the graphite target sputtering parameters and bias voltage unchanged (see step 6), high-power pulse and DC pulse magnetron co-sputtering deposition of Ag-doped conductive amorphous carbon layer C / Ag on the surface of the W-doped corrosion-resistant amorphous carbon layer, the deposition time is 30min;
[0135] (12) Finally, the graphite target, the Ag target and the heating device are turned off and cooled to room temperature in an argon atmosphere to complete the preparation of the corrosion-resistant conductive coating.
[0136] The test results show that the coating bonding force is 28N and the contact resistance with carbon paper is 5.3mΩcm 2 (1.4MPa); and at a temperature of 80°C, containing 0.1ppmF - Under the condition of 0.5M H2SO4 electrolyte solution and air flow, the self-corrosion current density after the dynamic potential test is 0.23μA / cm 2 After 10h of polarization test at 0.6V (vs. SCE), the corrosion current was 0.75μA / cm 2 .
[0137] Example 3
[0138] A method for preparing a corrosion-resistant conductive coating, the method comprising the following steps:
[0139] (1) First, a TC4 titanium alloy with a size of 50 mm × 50 mm × 0.1 mm was selected as the metal bipolar plate substrate, and its surface was polished to remove the surface oxide layer, and then ultrasonically cleaned in acetone, anhydrous ethanol and deionized water for 30 min in sequence to remove surface grease and impurities, and then dried and loaded into the furnace;
[0140] (2) Then, the chamber was evacuated to a vacuum of 5 × 10 -4 Pa, introduce argon Ar to keep the pressure at 0.20-0.25Pa, adjust the speed to 2r / min, apply -800V bias, and glow clean for 15min to remove the oxide layer and impurities on the surface of 316L stainless steel substrate and activate its surface;
[0141] (3) After the glow cleaning is completed, turn off the argon gas Ar and bias voltage to restore the vacuum inside the chamber to 5×10 -4 Pa below, ready to deposit metal base layer;
[0142] (4) Then, argon gas Ar was introduced and the pressure was maintained at 0.15-0.20 Pa, and then the Cr target was turned on and connected to a high-power pulse power supply. The power supply frequency of the Cr target was set to 400 Hz, the pulse width was 600 μs, the power was 3.0 kW, the substrate bias was set to -650 V, and the deposition temperature was 50°C. The metal Cr base layer was deposited on the surface of the TC4 titanium alloy substrate by high-power pulse magnetron sputtering of the Cr target for 10 min;
[0143] (5) Then, nitrogen N2 is introduced, and the flow ratio of nitrogen N2 to argon Ar is adjusted to 2:3 (the pressure is maintained at 0.20-0.25 Pa), the Cr target sputtering parameters and deposition temperature are kept unchanged (see step 4), and a conversion layer Cr / N is deposited on the surface of the metal Cr base layer for 8 min;
[0144] (6) Next, the graphite target is turned on and a high-power pulse power supply is connected at the same time. The power supply frequency of the graphite target is set to 500 Hz, the pulse width is 300 μs, and the power is 2.0 kW. The substrate bias voltage is reduced to -300 V (to avoid excessive bias voltage causing the carbon film structure to become loose and fall off). The Cr target sputtering parameters, gas flow rate, and deposition temperature are kept unchanged (see step 5). The conversion layer Cr / C / N is deposited on the surface of the conversion layer Cr / N for 5 min.
[0145] (7) After the conversion layer is completely deposited, turn off the Cr target and nitrogen N2, adjust the argon Ar flow rate to maintain the pressure at 0.15-0.20 Pa, and prepare to deposit the doped corrosion-resistant amorphous carbon layer;
[0146] (8) Next, turn on the W target and connect the DC pulse power supply, set the current of the W target to 15A, the pulse frequency to 300kHz, the pulse width to 75μs, keep the graphite target sputtering parameters and deposition temperature unchanged (see step 6), increase the bias voltage from -300V to -600V, and deposit for 5min; then, keep other parameters unchanged, adjust the bias voltage from -600V to -300V, and deposit for 5min; finally, keep other parameters unchanged, increase the bias voltage from -300V to -600V, and deposit for 5min;
[0147] (9) Afterwards, step (8) was repeated three times to obtain a three-layer unit W-doped corrosion-resistant amorphous carbon layer C / W, with a total deposition time of 45 min;
[0148] (10) After the deposition of the doped corrosion-resistant amorphous carbon layer is completed, the W target is turned off, and the Ar flow rate and pressure are maintained at 0.15-0.20 Pa to prepare for the deposition of the doped conductive amorphous carbon layer;
[0149] (11) Then, the Ag target was turned on and a DC pulse power supply was connected. The current of the Ag target was set to 10 A, the pulse frequency was set to 300 kHz, the pulse width was set to 75 μs, and the deposition temperature was increased from 50 °C to 300 °C (the increase in temperature can promote the formation of amorphous carbon sp 2 The content increases, which is beneficial to the conductive properties of the coating), keeping the graphite target sputtering parameters and bias voltage unchanged (see step 6), high-power pulse and DC pulse magnetron co-sputtering deposition of Ag-doped conductive amorphous carbon layer C / Ag on the surface of the W-doped corrosion-resistant amorphous carbon layer, the deposition time is 30min;
[0150] (12) Finally, the graphite target, the Ag target and the heating device are turned off and cooled to room temperature in an argon atmosphere to complete the preparation of the corrosion-resistant conductive coating.
[0151] The test results show that the coating bonding force is 29N and the contact resistance with carbon paper is 5.5mΩcm 2 (1.4MPa); and at a temperature of 80°C, containing 0.1ppmF - Under the condition of 0.5M H2SO4 electrolyte solution and air flow, the self-corrosion current density after the dynamic potential test is 0.14μA / cm 2 After 10h of polarization test at constant potential 0.6V (vs. SCE), the corrosion current was 0.62μA / cm 2 .
[0152] Compared with the prior art, the beneficial effects of the present invention also include:
[0153] (1) The corrosion-resistant conductive coating provided by the present invention has good conductivity and excellent corrosion resistance, and the corrosion current density can be as low as 0.14 μA·cm -2, contact resistance can be as low as 4.90mΩ·cm -2 , which are better than the US Department of Energy 2020 standard (self-corrosion current density <1μA·cm 2 , contact resistance <10mΩ·cm -2 ).
[0154] (2) The preparation method of the corrosion-resistant conductive coating provided by the present invention has the advantages of mature technology, high processing efficiency, easy control of preparation conditions, and continuous production, which can meet the market demand for mass production of metal bipolar plates for hydrogen fuel cells.
[0155] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a corrosion-resistant conductive coating, characterized in that: The following steps are involved: Argon gas is introduced, the metal target of the base element is turned on and a high-power pulse power supply is connected, and the metal base layer is deposited on the surface of the substrate by high-power pulse magnetron sputtering; After the metal base layer is deposited, nitrogen N2 is introduced immediately to deposit a conversion layer Me / N on the surface of the metal base layer by high-power pulsed magnetron sputtering; Turning on the carbon target and connecting to a high-power pulse power supply, depositing a conversion layer Me / C / N on the conversion layer Me / N by high-power pulse magnetron sputtering; After the conversion layer Me / C / N is deposited, the base metal target and nitrogen are turned off, the doped corrosion-resistant metal target is turned on and a DC pulse current is connected, and a doped corrosion-resistant amorphous carbon layer having a layered structure with alternating dense layers and loose layers is deposited on the surface of the conversion layer by high-power pulse and DC pulse magnetron co-sputtering, and a layered unit design is performed by adjusting the substrate bias voltage; After the deposition of the doped corrosion-resistant amorphous carbon layer is completed, the doped corrosion-resistant metal target is turned off, the doped conductive metal target is turned on and connected to a DC pulse power supply, and a doped conductive amorphous carbon layer is deposited on the surface of the doped corrosion-resistant amorphous carbon layer by high-power pulse and DC pulse magnetron co-sputtering; wherein, During the deposition of the metal base layer, the chamber pressure is maintained at 0.1-0.6 Pa, the high-power pulse power frequency is 100-800 Hz, the pulse width is 50-800 µs, the power is 1.0-5.0 kW, the substrate bias is -100--900 V, the deposition temperature is 20-400 ° C, and the deposition time is 5-20 min; During the deposition of the conversion layer Me / N, the flow ratio of nitrogen to argon is 1:(1-2), the chamber pressure is maintained at 0.2-0.9 Pa, the sputtering parameters and deposition temperature of the base metal target are consistent with those of the metal base layer, and the deposition time is 5-20 min; During the deposition of the conversion layer Me / C / N, the gas flow rate, the sputtering parameters of the base metal target, and the deposition temperature are all consistent with those of the deposition conversion layer Me / N; the power frequency of the carbon target is set to 50-600 Hz, the pulse width is 50-1000 µs, the power is 0.5-3.0 kW, the substrate bias is -100-500 V, and the deposition time is 5-20 min; During the deposition of the doped corrosion-resistant amorphous carbon layer, the chamber pressure is maintained at 0.1-0.9 Pa, the current of the doped corrosion-resistant metal target is 5-30 A, the pulse frequency is 50-600 kHz, the pulse width is 25-300 μs, the carbon target sputtering parameters and the deposition temperature are consistent with those of the deposited conversion layer; the substrate bias is alternately set to high and low bias, and the variation range is -100--900 V, and the total deposition time is 30-60 min; During the deposition process of the doped conductive amorphous carbon layer, the chamber pressure is maintained at 0.1~0.9Pa, the current of the conductive layer element metal target is 5~30A, the pulse frequency is 50~600kHz, the pulse width is 25~300μs, the carbon target sputtering parameters and the substrate bias are consistent with those of the deposited conversion layer; the deposition temperature is 200~400℃, and the deposition time is 30~60min.
2. The method for preparing the corrosion-resistant conductive coating according to claim 1, characterized in that: Each layered unit of the doped corrosion-resistant amorphous carbon layer is composed of high bias layers and low bias layers alternately, and contains n units in total, where n≥2.
3. The method for preparing the corrosion-resistant conductive coating according to claim 1, characterized in that: The base layer element Me is a metal element having a thermal expansion coefficient close to that of the metal bipolar plate matrix material; the conversion layer is at least one of a nitrogen-doped compound Me / N of the base layer element Me and a nitrogen-doped carbide Me / C / N of the base layer element Me; the doping element of the doped corrosion-resistant amorphous carbon layer is a corrosion-resistant metal element; the doping element of the doped conductive amorphous carbon layer is a conductive metal element.
4. The method for preparing the corrosion-resistant conductive coating according to claim 1, characterized in that: The thickness of the metal base layer is 5-20 nm, the thickness of the conversion layer is 10-60 nm, and the thickness of the doped amorphous carbon layer is 500-2000 nm.
5. The method for preparing the corrosion-resistant conductive coating according to claim 1, characterized in that: The conversion layer includes a conversion layer Me / N and a conversion layer Me / C / N, and the thickness of the conversion layer Me / N is 1% to 99% of the total thickness of the conversion layer, and the thickness of the doped corrosion-resistant amorphous carbon layer is 1% to 99% of the total thickness of the doped amorphous carbon layer.
6. A corrosion-resistant conductive coating, characterized in that: The corrosion-resistant conductive coating is obtained by the method for preparing the corrosion-resistant conductive coating according to any one of claims 1 to 5.
7. An application of the corrosion-resistant conductive coating as claimed in claim 6, characterized in that: The corrosion-resistant conductive coating is applied to metal bipolar plates of hydrogen fuel cells.
Citation Information
Patent Citations
Metal bipolar plate high-electric-conductivity and corrosion-resistance protective coating layer and preparation method and application thereof
CN110684946A
Amorphous carbon coating for fuel cell metal bipolar plate and preparation method of amorphous carbon coating
CN113991134A
